The influence of product, price, promotion, and place on the purchase decision of Xiaomi smartphones in STIE Muhammadiyah Jakarta students - Viniyati Maftuchach; Abdurrahman Rachman; Andri Gunawan; Sutar Sutar (Journal of Economics and Business Letters, 2022)
Along with the development of hardware technology such as mobile phones. The most consumptive market for mobile phone marketing is the Asian market, especially in Indonesia. More and more mobile phone manufacturers are popping up, this provides many choices for consumers. This research was conducted on campus 2 (Minangkabau) STIE Muhammadiyah Jakarta Jl. Minangkabau Raya No. 60 - South Jakarta. The time of this research was carried out in July 2020. The research design used in this study is causality research involve 100 respondents. the results of the T Test (Partial) it is known that the independent variable price (X2), Promotion (X3) partially has a significant influence on purchasing decisions, while the product variable (X1), place (X4) partially has no significant effect on purchase decision. From the results of the Partial Test (T test) it is known that from the four marketing mix the most dominant on purchasing decisions is the price variable (X2). Understanding marketing for companies is very important to realize the needs and desires of customers, determine the target market offered. Thus, marketing insights are also very beneficial for companies to provide the right products, services, and programs to serve the market to optimize sales.